Uwagi o redukcjonizmie - Kałuszyńska, Elżbieta (Filozofia Nauki, 1998)
In the article three types of reductionism are discussed: i) ontological reductionism (what happens on the «higher» level is causally determined by what happens on the «lower» level; ii) epistemological (the knowledge about the world can in principle be deduced from the physical equations); iii) methodological (explanation in terms of mechanics). These notions are beeing analysed from the point of view of the hypothesis, that reality should be viewed as an unstructured potentiality, which are «unfolded» in certain circumstances. Moderate ontological reductionism is the view, that phenomena from a certain level are the realisations of nature’s potentiality. Moderate epistemological reductionism is the view, that for (some) phenomena from the «higher» level, models in a more basic theory can be found.